Key factors to educational continuity and success of ciganos in Portugal - Magano, Olga (2021)
The goal of this article is to analyse the impact of specific public policies on the school trajectories of socially vulnerable Ciganos (Gypsies/Roma) who reside/live in the Metropolitan Areas of Lisbon and Porto. Through carrying out qualitative research, the analysis of key factors will allow us to understand the reasons behind school continuity and educational success of Ciganos, as well as the identity (re)configuration processes associated with the education paths of these individuals. We find that trajectories are not only intertwined with public policies and programmes, but also with other explanatory factors inherent to the individual,to the type of support he/she receives from his/her family, the presence of key figures in their lives, and the importance of peers and institutional factors inherent to the way public schools operate.